THE USE OF GRAPHS AND AUTOMATA TO THE CALCULATION OF DISCRETE AND CONTINUOUS BEAMS VIBRATIONS - Raspopov, O. S. (Science and Transport Progress, 2009)
The topological models for longitudinal and torsional oscillations of rod structures with various concentrated inclusions in distributed mass, stiffness of elastic medium and rod stiffness are done. The high efficiency of application of theory of graphs and automations into calculations of free oscillations of discrete-continual beams is shown.